Islet autoimmunity and progression to type 1 diabetes in the Finnish DIPP study: comparison between genetically susceptible children with and without an affected first-degree relative - Kuusela, Salla; Koskenniemi, Jaakko J.; Valtanen, Toni; Pokka, Tytti; Härkönen, Taina; Ilonen, Jorma; Lempainen, Johanna; Kyrönniemi, Anni; Toppari, Jorma; Knip, Mikael; Keskinen, Päivi; Veijola, Riitta (Springer Nature, 2026)
Aims/hypothesis
Islet autoimmunity during presymptomatic type 1 diabetes is heterogeneous. We hypothesised that a positive family history of type 1 diabetes is associated with specific characteristics of the autoimmune process resulting in clinical diabetes. In a prospective birth cohort study, we compared the initiation and evolution of islet autoimmunity and the rate of progression from islet autoimmunity to diabetes between children with and without a first-degree relative (FDR) with type 1 diabetes.
Methods
In the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) study, we prospectively followed children with HLA-conferred susceptibility from birth for the appearance of islet autoantibodies (IAA, GADA, IA-2A, ZnT8A), further development of islet autoimmunity, and progression to clinical diabetes. The presence of type 1 diabetes among their FDRs was recorded at the time of birth, and the family history data was updated during the follow-up period.
Results
Among a total of 1334 children with confirmed positivity for at least one islet autoantibody, 145 (10.9%) had one or more FDRs with type 1 diabetes at the time of birth (FDR+). During a median follow-up period of 8.6 years, FDRs of an additional 87 children developed type 1 diabetes (FDR− FDR+). At seroconversion, both FDR+ and FDR− FDR+ children were significantly more often positive for GADA and multiple autoantibodies than children without affected FDRs (FDR−). The seroconversion age was similar between the three groups (median 2.7 vs 2.1 vs 3.0 years in FDR+, FDR− FDR+ and FDR− children, respectively). During the follow-up period, FDR+ and FDR− FDR+ children more often had IAA, GADA, IA-2A and multiple autoantibodies than FDR− children, and progressed more frequently to diabetes (55.9 vs 57.5 vs 38.9%, respectively). Time from seroconversion to clinical diabetes was significantly shorter in FDR+ children compared with FDR− children (2.7 vs 3.6 years). Children with paternal type 1 diabetes at birth (n=71; i.e., the father had type 1 diabetes) were twice as often positive for multiple autoantibodies at seroconversion as those with maternal type 1 diabetes (n=50; i.e. the mother had type 1 diabetes) (39.4% vs 20.0%).
Conclusions/interpretation
At seroconversion, genetically susceptible children who had one or more FDRs with type 1 diabetes, especially an affected father, were more often positive for GADA and multiple islet autoantibodies. During the follow-up period, children with an affected FDR were more often positive for IAA, GADA and IA-2A, and progressed to clinical type 1 diabetes more often and faster than children without an affected FDR. These data should be considered when designing intervention and screening studies.